Conversion therapy for advanced intrahepatic cholangiocarcinoma with lenvatinib and pembrolizumab combined with gemcitabine plus cisplatin: A case report and literature review - Zhang, Wei; Luo, Chu; Zhang, Zun-Yi; Zhang, Bi-Xiang; Chen, Xiao-Ping (Frontiers in Immunology, 2023)
Background Intrahepatic cholangiocarcinoma (ICC) is a highly malignant biliary tumor. Patients with unresectable and advanced ICC have a poor prognosis with current gemcitabine-based chemotherapy. Combination therapy strategies based on immunotherapy have achieved promising results in various tumor types. Case presentation We reported a patient with unresectable ICC who received lenvatinib and pembrolizumab in combination with gemcitabine plus cisplatin (GP) chemotherapy and subsequently underwent radical liver resection. A 46-year-old male with a history of chronic hepatitis B and hypertension was diagnosed with ICC. Multiple liver tumors with ring-like enhancement were detected on abdominal contrast-enhanced CT and MRI. Enlarged lymph nodes were found in the hilar and retroperitoneal areas. The tumor was clinically staged as T2N1M0 (stage IIIB). Lenvatinib and pembrolizumab in combination with GP chemotherapy were adopted as first-line treatments for the patient. After six cycles of scheduled treatment, the diameter of the largest liver lesion and the number of liver lesions were markedly reduced. The level of the tumor marker CA19-9 decreased to a normal range. A partial response according to the mRECIST criteria was achieved without severe toxicities. Non-anatomical liver resection (segment 4b, 5,6 + segment 7 + segment 8), cholecystectomy and hilar lymph node dissection were performed one month after stopping combination therapy. Pathological examination confirmed a diagnosis of moderate-to-poorly differentiated ICC with lymph node metastasis. The patient has survived 15 months following resection of the tumors, with no evidence of local recurrence or distant metastasis. Conclusion Lenvatinib and anti-PD1 antibody pembrolizumab in combination with GP chemotherapy provided promising antitumor efficacy with reasonable tolerability, which may be a potentially feasible and safe conversion therapy strategy for patients with initially unresectable and advanced ICC.